2004
DOI: 10.1037/0022-006x.72.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Change in Cognitive-Behavioral Treatment of Panic Disorder: Evidence for the Fear of Fear Mediational Hypothesis.

Abstract: Numerous clinical trials have demonstrated the efficacy of cognitive-behavioral treatment (CBT) for panic disorder. However, studies investigating the mechanisms responsible for improvement with CBT are lacking. The authors used regression analyses outlined by R. M. Baron and D. A. Kenny (1986) to test whether a reduction in fear of fear (FOF) underlies improvement resulting from CBT. Pre- and posttreatment measures were collected from 90 CBT-treated patients and 40 wait-list control participants. Overall, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
130
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 43 publications
16
130
1
3
Order By: Relevance
“…NJREs might also be considered (and investigated) as a putative marker for OCD, in the same way in which the construct Anxiety Sensitivity (AS) is deemed a psychological marker of anxiety disorders in general and panic disorder in particular (e.g., Brown, Smits, Powers, & Telch, 2003;Rapee & Medoro, 1994;Schmidt, Lerew, & Jackson, 1997;Smits, Powers, Cho, & Telch, 2004; see literature on endophenotypes, Chamberlain et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…NJREs might also be considered (and investigated) as a putative marker for OCD, in the same way in which the construct Anxiety Sensitivity (AS) is deemed a psychological marker of anxiety disorders in general and panic disorder in particular (e.g., Brown, Smits, Powers, & Telch, 2003;Rapee & Medoro, 1994;Schmidt, Lerew, & Jackson, 1997;Smits, Powers, Cho, & Telch, 2004; see literature on endophenotypes, Chamberlain et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Internal validity is good (Cronbach's alpha from .82-.92; Alpers and Pauli, 2002). Studies have found the ASI to mediate treatment outcome in PD (Smits, Powers, Cho, Telch, 2004). In this study, the ASI was examined as a predictor of treatment outcome.…”
Section: Assessmentmentioning
confidence: 98%
“…The hypothesis that the effects of CBT would be mediated by changes in orthostatic panic severity was tested in accordance with the analytic steps outlined by Baron and Kenny [1986] [for a description of the same analytic strategy as used in another study, see Smits et al, 2004]:…”
Section: Statistical Analysesmentioning
confidence: 99%